Selectivity of Threefold Symmetry in Epitaxial Alignment of Liquid Crystal Molecules on Macroscale Single-Crystal Graphene - Shen, Tian Zi; Hong, Seung Ho; Lee, Jae Hyun; Kang, Seog Gyun; Lee, Bomi; Whang, Dongmok; Song, Jang Kun (Advanced Materials, 2018)
Epitaxial alignment of organic liquid crystal (LC) molecules on single-crystal graphene (SCG), an effective epitaxial molecular assembly template, can be used in alignment-layer-free liquid crystal displays. However, selectivity among the threefold symmetric easy axes of LCs on graphene is not well understood, which limits its application. Here, sixfold symmetric radial LC domains are demonstrated by dropping an LC droplet on clean SCG, which reveals that the graphene surface does not have an intrinsic preferential direction. Instead, the first contact geometry of the LC molecules determines the direction. Despite its strong anchoring energy on graphene, the LC alignment direction is readily erasable and rewritable, contrary to previous understanding. In addition, the quality of the threefold symmetric alignment is sensitive to alien residue and graphene imperfections, which can be used to detect infinitesimal impurities or structural defects on the graphene. Based on this unique epitaxial behavior of LCs on SCG, an alignment-layer-free electro-optical LC device and LC alignment duplication, which can result in practical graphene-based flexible LC devices, are realized.
Keywords: Alignment layers; Anchoring energies; Epitaxial alignment; Epitaxial behavior; Liquid crystal molecules; Molecular assembly; Structural defect; Three-fold symmetry; liquid crystals; molecular assembly; single-crystal graphene